2009
DOI: 10.1002/bdra.20593
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal alcohol exposure on the morphological characteristics of spinal motoneurons

Abstract: Prenatal exposure to alcohol showed cytotoxic effects whereby it adversely affected both motoneuron growth and differentiation in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A study on prenatal alcohol intake has shown that the number and the morphology of MN were significantly reduced. The authors highlighted the detrimental effects of EtOH (neurotoxicity and oxidative stress) in this critical period of the development of the nervous system [63].…”
Section: Discussionmentioning
confidence: 99%
“…A study on prenatal alcohol intake has shown that the number and the morphology of MN were significantly reduced. The authors highlighted the detrimental effects of EtOH (neurotoxicity and oxidative stress) in this critical period of the development of the nervous system [63].…”
Section: Discussionmentioning
confidence: 99%